The Width of the Intra-European Economic Borders - de Serres, Alain (OECD Publishing, 2001)
This paper first provides a brief overview of the literature on market segmentation and then presents an empirical exercise that sheds more light on the significance of border effects across European countries. The literature suggests that integration in the EU goods and financial markets is typically more advanced than among the other OECD countries. On the other hand, integration in Europe remains significantly lower than that observed between regions within countries. The empirical exercise is based on a set of comparable price data of tradeable goods collected just before the launch of the single currency. The paper finds that for a given distance, crossing national borders adds significantly to the price differential across European cities. However, this border effect is substantially smaller than the one found in previous estimates focusing on European and North American cities, which were based on the comparison of much broader price indices such as the consumer price index ...
Keywords: Economics